Long-term use and cost-effectiveness of secondary prevention drugs for heart disease in Western Australian seniors (WAMACH): a study protocol. Issue 9 (18th September 2014) - Gunnell, Anthony S; Knuiman, Matthew W; Geelhoed, Elizabeth; Hobbs, Michael S T; Katzenellenbogen, Judith M; Hung, Joseph; Rankin, Jamie M; Nedkoff, Lee; Briffa, Thomas G; Ortiz, Michael; Gillies, Malcolm; Cordingley, Anne; et al.
Abstract : Introduction: Secondary prevention drugs for cardiac disease have been demonstrated by clinical trials to be effective in reducing future cardiovascular and mortality events (WAMACH is the W estern A ustralian M edication A dherence and C osts in H eart disease study). Hence, most countries have adopted health policies and guidelines for the use of these drugs, and included them in government subsidised drug lists to encourage their use. However, suboptimal prescribing and non-adherence to these drugs remains a universal problem. Our study will investigate trends in dispensing patterns of drugs for secondary prevention of cardiovascular events and will also identify factors influencing these patterns. It will also assess the clinical and economic consequences of non-adherence and the cost-effectiveness of using these drugs. Methods and analysis: This population-based cohort study will use longitudinal data on almost 40 000 people aged 65 years or older who were hospitalised in Western Australia between 2003 and 2008 for coronary heart disease, heart failure or atrial fibrillation. Linking of several State and Federal government administrative data sets will provide person-based information on drugs dispensed precardiac and postcardiac event, reasons for hospital admission, emergency department visits, mortality and medical visits. Dispensed drug trends will be described, drug adherence measured and their association with future all-cause/cardiovascular events will be estimated. The cost-effectiveness of these long-term therapies for cardiac disease and the impact of adherence will be evaluated. Ethics and dissemination: Human Research Ethics Committee (HREC) approvals have been obtained from the Department of Health (Western Australian #2011/62 and Federal) and the University of Western Australia (RA/4/1/1130), in addition to HREC approvals from all participating hospitals. Findings will be published in peer-reviewed medical journals and presented at local, national and international conferences. Results will also be disseminated to consumer groups.